2022
DOI: 10.47191/ijmscrs/v2-i2-10
|View full text |Cite
|
Sign up to set email alerts
|

Breakthrough infections due to SARS-CoV-2 Wild type, the Delta variant and the Omicron variant in early fourth wave of epidemics in Myanmar

Abstract: The “severe acute respiratory syndrome coronavirus type 2” (SARS-CoV-2) is also known as “coronavirus disease 19” (COVID-19). It originated in Wuhan, Hubei province, People’s Republic of China, in December 2019; and, it spread worldwide causing a global pandemic. Genetic variants of SARS-CoV-2 have been emerging and circulating around the world throughout the COVID-19 pandemic namely the original (wild-type), the Alpha variant, the Beta variant, the Delta variant, and the Gamma variant. In third wave, the noto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Previous report from Myanmar revealed that one in four physicians who had two doses of vaccine had BTI (Pyar et al, 2021). Moreover, BTI due to the Omicron variant were found in early 2022 in Myanmar (Pyar, 2022). Therefore, this study aimed to assess the prevalence of BTI in fourth wave among HCW and their family members, the severity and the protective effect of COVID-19 vaccine in Myanmar.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous report from Myanmar revealed that one in four physicians who had two doses of vaccine had BTI (Pyar et al, 2021). Moreover, BTI due to the Omicron variant were found in early 2022 in Myanmar (Pyar, 2022). Therefore, this study aimed to assess the prevalence of BTI in fourth wave among HCW and their family members, the severity and the protective effect of COVID-19 vaccine in Myanmar.…”
Section: Introductionmentioning
confidence: 97%
“…Table (1) : Clinical characteristics and outcomes of physicians and family members infected in 4th wave of COVID-19 Pandemic (N=236)DiscussionFourth wave of COVID-19 infection began in Myanmar in January 2022; the Omicron variant was imported from neighboring countries(Pyar, 2022). Fourth wave was mainly due to the Omicron variant as surveillance of nasopharyngeal swab PCR revealed the Omicron variant(Pyar, 2022). COVID-19 vaccine Programme has been launching since 2021; and, fifty percent of total population received two doses of vaccine.…”
mentioning
confidence: 99%